2014
DOI: 10.1136/bcr-2013-201698
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral transient osteoporosis of the hip in a 20-year-old man

Abstract: Transient osteoporosis is a rare musculoskeletal condition that has been reported in pregnant women and middle-aged men. We present a bilateral case in a young man. A 20-year-old man presented with spontaneous onset left hip pain. Investigations excluded other differential diagnoses such as infection or fracture. The pain resolved completely; 6 months later the patient presented with a similar episode of pain in the contralateral hip. This also resolved spontaneously. Doctors need to be aware of the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Our case had no remarkable plain X-ray findings at one week after symptom onset, and some investigators reported normal plain X-ray findings in the early stage of TOH [ 11 , 12 ]. Magnetic resonance imaging shows diffuse bone marrow edema with increased signal on T2-weighted images and decreased signal on T1-weighted images in TOH [ 13 ]. Characteristic findings of TOH in magnetic resonance imaging include the complete resolution of abnormal signal intensity over several weeks [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our case had no remarkable plain X-ray findings at one week after symptom onset, and some investigators reported normal plain X-ray findings in the early stage of TOH [ 11 , 12 ]. Magnetic resonance imaging shows diffuse bone marrow edema with increased signal on T2-weighted images and decreased signal on T1-weighted images in TOH [ 13 ]. Characteristic findings of TOH in magnetic resonance imaging include the complete resolution of abnormal signal intensity over several weeks [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 ). The total bone density was 1.019 g/cm 2 (T-score 0.6, Z-Score 0.6). At this second presentation, bone scintigraphy was not obtained.…”
Section: Case Reportmentioning
confidence: 98%
“…He was a physically fit person and worked as an office staff. His body weight was 78kg and height 178cm with body mass index 24.6 kg/m 2 . On physical examination, there was a limping gait and positive on the Patrick’s test of the right hip.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations